New indicators of illegal drug use to compare drug user populations for policy evaluation - Francesco Fabi; Alessia Mammone; Carla Rossi (Epidemiology, Biostatistics and Public Health)
Background: New trends in drug consumption show a trend towards higher poly-use. Epidemiological indicators presently used are mostly based on the prevalence of users of the “main” substances and the ranking of harm caused by drug use is based on a single substance analysis. Methods: In this paper new indicators are proposed; the approach consider the segmentation of the population with respect to the frequency of use in the last 30 days and the harm score of the various substances used by a poly-user. Scoring is based on single substance score table reported in recent papers and principal component analysis is applied to reduce dimensionality. Any user ischaracterized by the two new scores: frequency of use score and poly-use score. Results: The method is applied to the drug user populations interviewed in Communities and Low Threshold Services within the Problem Drug Use 2012 survey in four different European countries. The comparison of the poly-use score cumulative distributions gives insight about behavioural trends of drug use and also evaluate the efficacy of the intervention services. Furthermore, the application of this method to School Population Survey 2011 data allows a definition of the expected behaviour of the poly-drug score for the General Population Survey to be representative. Conclusions: In general, the method is simply and intuitive, and could be applied to surveys containing questions about drug use. A possible limitations could be that the median is chosen for calculating the frequency of use score in questionnaires containing the frequency of drug use in classes.